FACTORS RELATED TO THE USE OF PERSONAL PROTECTIVE EQUIPMENT IN SHIPYARD WELDERS - Rizky Agung Firnando (Universitas Darussalam Gontor, 2018)
Welders can be exposed to occupational hazard. One way to prevent is by using proper PPE.There are many factors that relate to the use of PPE in welders. This was an observational analytic study with cross sectional design. The population of the study was welders of PT. X's Commerce Ship Division. The number of the sample was 52 welders who was selected randomly. Data were collected by means of questionnaires and observation checklist. The results of this study were welders of PT. X's Commerce Ship Division used enough personal protective equipment. There was significant correlation between antecedent variable (i.e. perceptions about potential hazards and PPE usage) with the used of PPE. Consequence variable (i.e. reward) was significantly correlate with the used of PPE. It can be concluded that perceptions about potential hazards and PPE usage,and reward are factors that relate to the use of PPE in welders of PT. X Commercial Ship Division. The suggestion is evaluate the reward system for the suitability of the use of personal protective equipment in welders.Keyword: determinant factors, the use of personal PPE, welders